Computation of the scattered fields from an overfilled cavity embedded in a perfectly conducting ground plane - Saynak, U.; Kizilay, A. (TAYLOR & FRANCIS LTD, 2016)
A decomposition method is applied to solve the electromagnetic scattering from an overfilled cavity embedded in a perfectly electric conducting (PEC) ground plane. The surface equivalence principle is used with the decomposition method to obtain a set of electric field integral equations (EFIEs) for the currents on the overfilled cavity surfaces and the perturbation current on the portion of PEC ground plane surface near the cavity. The Method of Moments (MoM) is used to solve the EFIEs in the frequency domain to obtain the scattered electric field. The method is presented with examples for TMz polarization and the results are compared with various other solution methods.
Keywords: Method of moments; computational electromagnetics; overfilled cavity; equivalency principle; ELECTROMAGNETIC SCATTERING; INTEGRAL-EQUATIONS; TM-SCATTERING; GROOVE; TROUGH; Engineering; Physics